Periodontal Biological Events Associated with Orthodontic Tooth Movement: The Biomechanics of the Cytoskeleton and the Extracellular Matrix. (13th August 2015) - Feller, L.; Khammissa, R. A. G.; Schechter, I.; Moodley, A.; Thomadakis, G.; Lemmer, J.
Abstract : The mechanical stimuli generated by orthodontic forces cause deformation of extracellular matrices and cells, vascular changes, inflammation, and the release of active biological agents generating a complex multifactorial sequence of biological events culminating in bone remodelling enabling orthodontic tooth movement. Orthodontic forces on the teeth generate stresses in periodontal tissues according to a number of variables including the type (continuous, interrupted, or intermittent), magnitude, direction, and frequency of the applied load. Whether the strain is compressive or tensile determines whether bone deposition or bone resorption will occur. The mechanically induced strains mediate structural changes in extracellular matrices and in cells, consequently affecting cellular gene expression and function. In the extracellular matrix, mechanosensing molecules integrated into the structure of various proteins can be activated upon load-induced protein unfolding. These specialized molecules have the capacity to sense and then to convert microenvironmental biomechanical stimuli into intracellular biochemical signals that interact to generate a coordinated tissue response. It is also possible that the applied force may directly cause nuclear deformation with configurational changes in chromatin, thus influencing gene expression. In this review article we summarize the current general concepts of mechanotransduction influencing the remodelling of periodontal tissues thus enabling tooth movement in response to applied orthodontic loads.